Attitudes towards Heroin Addicts and Addiction in Inter-War Greece. (November 2014) - Gotsinas, Kostis
Abstract : This article concentrates on the 'drug scare' caused by the introduction of heroin to Greece in the inter-war period. It will first retrace the story of heroin's introduction into the Greek drug scene and assess the reasons for its speedy diffusion among drug users. Following this, it will examine some central themes in the discourse on drugs and heroin in particular, such as the actual or projected harm caused to individuals, society, or the nation as a whole. Then the focus will shift to perceptions of heroin and its users, considering broader debates which circulated in Greek inter-war society, for example, the country's identity and its position within two parallel and interrelated conceptual frameworks: traditional vs. modern and 'East' vs. 'West'. The paper will conclude by addressing drug users' self-representations that were influenced, to a certain degree, by the prevailing approaches to drug addiction.